From New Emerging to New Emerging Markets Stuck in between Opportunity and Risk: internationalization of Turkish Firms in Romania - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The focus of this paper is to study how MNCs from new emerging markets manage the opportunity development in other new emerging markets. The aim is to propose a theoretical frame based on business network theory holding the concepts of opportunity development, risk, knowledge, and commitment used to analyze the Turkish firm's behavior in Romania. With the infusion of risk tolerance concept, the study contributes new knowledge to the internationalization model and aids understanding of how new MNCs develop opportunities. It enriches network theory as it unfolds the role of an actor's risk perception and the role of financial resources.
Keywords: Commitment; knowledge; international opportunity development; political actions; risk tolerance; Turkey and Romania; FOREIGN DIRECT-INVESTMENT; SERVICE FIRMS; PROCESS MODEL; KNOWLEDGE; MULTINATIONALS; ENTREPRENEURSHIP; DETERMINANTS; PERFORMANCE; COMPANIES; CAPABILITIES